Algae : anatomy, anatomy, biochemistry, and biotechnology - Barsanti, Laura; Gualtieri, Paolo (CRC Press, 2014)
A single-source reference on the biology of algae, Algae: Anatomy, Biochemistry, and Biotechnology, Second Edition examines the most important taxa and structures for freshwater, marine, and terrestrial forms of algae. Its comprehensive coverage goes from algae's historical role through its taxonomy and ecology to its natural product possibilities. The authors have gathered a significant amount of new material since the publication of the first edition. This completely revised second edition contains many changes and additions including the following